Cellular Degradation of Free and Inhibitor-bound Tissue-type Plasminogen Activator - Camani, Chantal; Gavin, Olivier; Kruithof, Egbert K. O. (Thrombosis and Haemostasis, 2000)
The low density lipoprotein receptor-related protein (LRP) is a multiligand clearance receptor that removes free tissue-type plasminogen activator (t-PA) or complexes of t-PA with plasminogen activator inhibitor type 1 (PAI-1) from the blood circulation or the pericellular space. Co-receptors are essential for LRP-mediated clearance of several ligands (e.g. glycosaminoglycans for thrombin/protease nexin and lipoprotein lipase, and the urokinase receptor for urokinase/PAI-1 complexes). The present study was undertaken to investigate whether LRP-mediated t-PA clearance requires a co-receptor as well.In five cell lines from different organs and species degradation of t-PA and t-PA/PAI-1 was mediated by LRP (or LRP-like receptors). No degradation of t-PA and t-PA/PAI-1 occurred in THP-1 or U-937 human monocyte-like cells, despite the presence of functional LRP. As glycosaminoglycans can bind t-PA and PAI-1 we investigated whether they are involved in t-PA/PAI-1 degradation. Pre-treatment of COS cells or HT1080 cells with chlorate, an inhibitor of glycosaminoglycan sulfation, did not decrease t-PA/PAI-1 degradation. Furthermore, CHO cells genetically deficient in glycosaminoglycans efficiently degraded t-PA/PAI-1. Thus it is unlikely that glycosaminoglycans are co-receptors for degradation of t-PA or t-PA/PAI-1.This study indicates that THP-1 and U-937 cells lack a critical component (co-receptor?) for the LRP-mediated degradation of t-PA.Abbreviations: LRP, low density lipoprotein receptor-related protein; PAI-1, plasminogen activator inhibitor type 1; RAP, receptor-associated protein; t-PA, tissue-type plasminogen activator; u-PA, urokinase; u-PAR, urokinase receptor.
Keywords: Clearance; t-PA; PAI-1; LRP; thrombin